Differential vibrating-wire strain gauge for concrete deformation measurements - Kanciruk, Adam; Matus, Elżbieta (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The basic measuring element of vibrating-wire strain gauges is a steel piano wire, functioning in the elastic range. This element is constantly under tension. Therefore, its material gradually deforms permanently. This deformation causes its stress to relax. This relaxation results in measurement errors of the strain gauges. This error, as demonstrated by both in situ and laboratory tests, can reach values of even several percent of the strain gauge measuring range (FSR) over periods of 10 years. Therefore, a concept of a differential strain gauge was proposed, for the construction of which two measuring wires would be used. Changing the input value of the strain gauge, i.e. a displacement of one of its anchors in relation to the other one would cause one wire to lengthen while the other wire shortened identically. The measured displacement would be calculated based on the difference in the frequency of the wire vibrations. In this way, the influence of the simultaneous relaxation of the wires on the measurement result would be greatly reduced. Based on this concept, a prototype differential strain gauge for measuring concrete deformation was realized. In addition to two wires, it also contains two electromagnets, placed together with the wires in a common body-housing. After the strain gauge was assembled, its first tests were carried out under laboratory conditions.